Analısıs Faktor-Faktor Yang Mempengruhı Purchase Intentıon Onlıne Delıvery Food Pada Food Brand Internatıonal - Agustina Fitrianingrum; Chelika Siagian (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The presence of online transportation, the increasing needs of the community, opens opportunities for International Food Brand businesses to be present in the food industry in Indonesia. The purpose of this study was to determine the effect of customer attitude towards online delivery food on purchase intention for international food brands. This study analyzes the factors that influence purchase intention in online food delivery, namely: Food Quality, Service Quality, Price, Social Media, and Social Media. In the research model, the researcher conducts an online survey to collect data. This study uses Partial Least Square or PLS. The results of this study found that all hypotheses have a significant relationship and have a positive relationship with Purchase Intention Online Delivery Food at International Food Brands.